2018
DOI: 10.14744/eej.2018.69077
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Root Canal Fillings Performed by Undergraduate Students and the Related Factors on the Treatment Outcome: A 2- to 5-Year Follow-Up

Abstract: Radiographic technical quality of root canal fillings performed by undergraduate students and the related factors on the treatment outcome: A 2-to 5-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…This result is similar to Unal et al 12 (2011), Lynch et al 17 (2006), and Vukadinov et al 18 (2014). However, the result of the present study is not in agreement with others that found success rates between 10-54% 2,7,15,16,19,20 . These studies include molars in the evaluation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is similar to Unal et al 12 (2011), Lynch et al 17 (2006), and Vukadinov et al 18 (2014). However, the result of the present study is not in agreement with others that found success rates between 10-54% 2,7,15,16,19,20 . These studies include molars in the evaluation.…”
Section: Discussioncontrasting
confidence: 99%
“…The root canal filling of each root was radiographically assessed in terms of the length and density of the filling materials using the criteria suggested in previous studies 15,16 . The root canal filling was classified as adequate if the root filling ended 0-2mm of the radiographic apex and there were no space/voids between root filling and root canal wall (Table 1).…”
Section: Fillingsmentioning
confidence: 99%
“…The students in the face‐to‐face group were more successful at preparing the cavities in all parameters, except for the removal of the pulp ceiling. Similar to previous studies, a periapical X‐ray examination was performed to evaluate the quality of root canal fillings 28–30 . The data indicated that the root canal fillings in the face‐to‐face training group ended at an ideal apical distance and were significantly more homogeneous than those in the online group.…”
Section: Discussionmentioning
confidence: 59%
“…Similar to previous studies, a periapical X-ray examination was performed to evaluate the quality of root canal fillings. [28][29][30] The data indicated that the root canal fillings in the face-to-face training group ended at an ideal apical distance and were significantly more homogeneous than those in the online group. The degree of taper that the two groups examined was also similar.…”
Section: Discussionmentioning
confidence: 96%
“…A study from the United Kingdom showed that teaching methods developed during the last decade led to a wider variation of methods [2]. Despite this, several studies point out that the quality of root canal treatments performed by undergraduate students is often not satisfactory [3,4,5,6,7,8]. Thereby, the way of teaching endodontics has a major influence on the quality of root canal treatments performed by students [9].…”
Section: Introductionmentioning
confidence: 99%